Study on the size effect of rock elastic modulus considering the influence of joint roughness - Hu, Gaojian; Wang, Bin; Guo, Wenbing; Xing, Yuan; Zhou, Junxia; Zha, Lanchang; Meng, Shiyu (Frontiers in Materials, 2024)
The elastic modulus of rocks is a measure of the ability of rocks to resist elastic deformation. It is related to the size of rocks and can effectively measure the internal physical and mechanical strength of rocks. The development of joint fractures is the main reason for the size effect of rocks. Therefore, exploring the influence of joint roughness on the elastic modulus of rocks of different sizes is of great significance in mining rock mechanics. The article investigates the size effect of joint roughness on elastic modulus of rocks by establishing simulation schemes for 30 working conditions. By analyzing the stress-strain curves of rocks with different roughness and sizes, the deformation and failure patterns of rocks with different sizes were obtained. Research has found that the elastic modulus of rocks is in a power function relationship with joint roughness, while the elastic modulus of rocks is negatively exponentially related to rock size; The characteristic elastic modulus of rocks is in a power function relationship with joint roughness. The above relationships not only reveal the variation of rock elastic modulus with size, but also reveal the influence of joint roughness on elastic modulus, providing important basis for understanding the stability of mining rock engineering.